Oligonucleotide‐Based Mimetics of Hepatocyte Growth Factor. (23rd November 2015) - Ueki, Ryosuke; Ueki, Ayaka; Kanda, Naoto; Sando, Shinsuke
Abstract: Oligonucleotide‐based hepatocyte growth factor (HGF) mimetics are described. A DNA aptamer to Met, a cognate receptor for HGF, was shown to induce Met activation when used in dimer form. The most potent aptamer dimer, ss‐0, which was composed solely of 100‐mer single‐stranded DNA, exhibited nanomolar potency. Aptamer ss‐0 reproduced HGF‐induced cellular behaviors, including migration and proliferation. The present work sheds light on oligonucleotides as a novel chemical entity for the design of growth factor mimetics.